Solar‐induced chlorophyll fluorescence is strongly correlated with terrestrial photosynthesis for a wide variety of biomes: First global analysis based on OCO‐2 and flux tower observations. (4th June 2018) - Li, Xing; Xiao, Jingfeng; He, Binbin; Altaf Arain, M.; Beringer, Jason; Desai, Ankur R.; Emmel, Carmen; Hollinger, David Y.; Krasnova, Alisa; Mammarella, Ivan; Noe, Steffen M.; Ortiz, Penélope Serrano; et al.
Abstract: Solar‐induced chlorophyll fluorescence (SIF) has been increasingly used as a proxy for terrestrial gross primary productivity (GPP). Previous work mainly evaluated the relationship between satellite‐observed SIF and gridded GPP products both based on coarse spatial resolutions. Finer resolution SIF (1.3 km × 2.25 km) measured from the Orbiting Carbon Observatory‐2 (OCO‐2) provides the first opportunity to examine the SIF–GPP relationship at the ecosystem scale using flux tower GPP data. However, it remains unclear how strong the relationship is for each biome and whether a robust, universal relationship exists across a variety of biomes. Here we conducted the first global analysis of the relationship between OCO‐2 SIF and tower GPP for a total of 64 flux sites across the globe encompassing eight major biomes. OCO‐2 SIF showed strong correlations with tower GPP at both midday and daily timescales, with the strongest relationship observed for daily SIF at the 757 nm ( R 2 = 0.72, p < 0.0001). Strong linear relationships between SIF and GPP were consistently found for all biomes ( R 2 = 0.57–0.79, p < 0.0001) except evergreen broadleaf forests ( R 2 = 0.16, p < 0.05) at the daily timescale. A higher slope was found for C4 grasslands and croplands than for C3 ecosystems. The generally consistent slope of the relationship among biomes suggests a nearly universal rather than biome‐specific SIF–GPP relationship, and this finding is an important distinction and simplification compared to previous results. SIF was mainly driven by absorbed photosynthetically active radiation and was also influenced by environmental stresses (temperature and water stresses) that determine photosynthetic light use efficiency. OCO‐2 SIF generally had a better performance for predicting GPP than satellite‐derived vegetation indices and a light use efficiency model. The universal SIF–GPP relationship can potentially lead to more accurate GPP estimates regionally or globally. Our findings revealed the remarkable ability of finer resolution SIF observations from OCO‐2 and other new or future missions (e.g., TROPOMI, FLEX) for estimating terrestrial photosynthesis across a wide variety of biomes and identified their potential and limitations for ecosystem functioning and carbon cycle studies. Abstract : We conducted the first global analysis of the relationship between solar‐induced chlorophyll fluorescence (SIF) and gross primary productivity (GPP) based on OOC‐2 and flux tower observations. Strong linear relationships between SIF and GPP at the ecosystem scale were found for all eight biomes except evergreen broadleaf forests. The nearly universal rather than biome‐specific SIF–GPP relationship can potentially lead to more accurate GPP estimates globally. OCO‐2 SIF can generally better estimate GPP than satellite‐derived vegetation indices and light use efficiency models. Our findings revealed the potential of finer‐resolution SIF observations in ecosystem functioning and carbon cycling studies and model benchmarking efforts.